Fault in criminal law a research companion - Adams, Verity; Reed, Alan; Simpson, Bethany; Bohlander, Michael 1962- (Substantive issues in criminal law, 2023)
"This volume presents a comparative examination of the issue of Fault in Criminal Law. Extant law reveals significant problems in adoption of consistent approaches to doctrinal and theoretical underpinnings of fault liability and culpability thresholds in Criminal Law. This has been exemplified by a plethora of recent jurisprudential authorities revealing varying degrees of confusion and vacillation. This collection focuses on fault liability for inculpation with contributions from leading specialists from different jurisdictions presenting alternative perspectives. The book addresses three specific elements within the arena of fault, embracing an overarching synergy between them. This structure facilitates an examination of UK provisions, with specialist contributions on domestic law, and in contrasting these provisions against alternative domestic jurisdictions as well as comparative contributions addressing a particularised research grid for content. The comparative chapters provide a wider background of how other legal systems treat a variety of specialised issues relating to fault elements in the context of the Criminal Law. With contributions from leading experts in the field, the book will be an invaluable resource for researchers, academics and practitioners working in this area"--